Optimalisasi Videografis untuk Meningkatkan Kecakapan Statistik di Desa Panca Mukti - Firdaus Firdaus (Indonesian Journal of Community Empowerment and Service (ICOMES), 2026)
Panca Mukti Village in Pondok Kelapa Subdistrict, Central Bengkulu Regency, has shown progress in the use of information technology through its official website, which provides information on development, administration, and population data. However, the presentation of data, which is still limited to tables and text, makes it difficult for the community and village officials to understand the information quickly and comprehensively. This Community Service Program aims to improve statistical skills and the effectiveness of information delivery through videographic media using the Canva application. Training was provided to the village officials and youth organization members to convert static data into communicative and attractive visual content. The activity was evaluated using pre-test and post-test methods, which were analyzed using a paired t-test. The evaluation results showed a significant difference between participants' knowledge before and after the training. These findings reflect an increase in the competence of village officials in processing data and presenting information in an attractive videographic.